Plasma-liquid system with reverse vortex flow of “tornado” type (TORNADO-LE) - Nedybaliuk, O.A.; Chernyak, V.Ya.; Olszewski, S.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The results of experimental investigations of the plasma in plasma-liquid system with reverse vortex flow of “tornado” type are presented. Volt-ampere characteristic of discharge in the current range from 200 to 400 mA were measured. Emission spectra of plasma in range from 200 to 1100 nm were measured. Excitation temperatures (electronic Te*, vibrational Tv* and rotational Tr*) were obtained. Emission spectra of hydroxyl OH were calculated.